The Relationship Between Mothers' Knowledge Levels about Immunization and the Completeness of Basic Immunization in Toddlers - Riski Muhammad Akbar Kaharuddin; Devi Cynthia Dewi; Nur Asmah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Immunization is an effective way to prevent infectious diseases and reduce morbidity and mortality in toddlers. Mothers' knowledge of basic immunizations plays a crucial role in determining the completeness of their child's immunizations. This study aims to determine the relationship between mothers' knowledge of immunizations and the completeness of basic immunizations in toddlers. This study is descriptive analytical with a cross-sectional approach. Sectional. The study population was all mothers with toddlers aged 12–59 months in the working area of Community Health Center X in 2025 with a sample of 100 respondents taken by purposive sampling. Data were collected using an immunization knowledge questionnaire and a KIA book observation sheet. Data analysis was carried out univariately and bivariately using the Chi- Square test. The results showed that most mothers had good knowledge (62%), and 68% of toddlers had complete basic immunizations. The Chi- Square test showed a p value = 0.002 (<0.05) which means there is a significant relationship between the level of maternal knowledge about immunization and the completeness of basic immunizations in toddlers. It was concluded that the higher the level of maternal knowledge, the more complete the basic immunizations in toddlers. It is hoped that health workers will increase public education about the importance of immunization through counseling and attractive information media.